IMPLEMENTASI PROGRAM KEAGAMAAN DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA - Mukhlishah; Muhammad Fadlani Salam; Iim Ibrohim; Hernawati; Nur Gina Khairunnisa (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2024)
The purpose of the research is to analyze the implementation of religious programs and student morals at SMK Medina Bandung City. The implemented religious program is a school effort in shaping students' morals. This research uses a qualitative approach, the method in this research is descriptive analytic Data collection techniques use interviews, observation, and documentation, while data analysis uses descriptive analysis with three stages of analysis, namely data reduction, data presentation, and conclusion drawing. The results showed that: 1) the form of religious programs: recitation of asmaul husna, tadarus together, dhuha prayer, dzuhur prayer in congregation, tahsin and tahfidz Al-Qur'an. 2) in the implementation of religious programs, some are carried out every day, some are only twice a week. 3) Supporting factors: cooperation between teachers, school curriculum and support from Nahdliyin. Inhibiting factors: limited facilities and diverse family and social environments of students.4). the results can be seen from the emergence of an attitude of monotheism, fear of God, tawakal, refraining from forbidden things, trustworthiness or honesty.